Daily/weekly scheduler for staff / Cheah Li Wei - Cheah , Li Wei (2003)
Daily/weekly scheduler for staff (DWS) is a web-based system that will be implemented in internet environment. It is developed using open source concept according to World Wide Web standard which is cross-platform and and database independent. The objectives of DWS are to implement a computerized and efficient scheduling system in a company. The system will help to manage the scheduler information more systematically and effectively. The information includes staffs and supervisors profile and staff scheduler. DWS system is divide into four modules: Administrator module, Supervisor module, Staff module and General module. Basically, administrator module is about database admin. Besides, the administrators also assign staff and supervisor according to the department. While is supervisor module, supervisor can view staffs scheduler by daily/weekly/monthly. Besides, supervisor can also writes comments against the scheduler. For the staff module, staffs can write comments against the scheduler. For the staff module, staffs can write schedule (planning) in their work. This will make sure staffs can finish their work within the scheduler time. The features and benefits of this system are to manage staffs works systematically more efficient and secure web-based system.